Feasibility Assessment of Mudstone Aggregate as an Alternative Material for Colored Asphalt Pavement in South Korea - Je Won Kim; Carlo Elipse (Applied Sciences)
Colored asphalt pavements have been implemented in South Korea to enhance visibility and lane distinction; however, color fading, accelerated deterioration, and increased pothole occurrence have been noticed. As a solution, alternative materials that can be used for the construction of colored asphalt pavements are being explored. This study evaluates the feasibility of using mudstone aggregate in constructing colored asphalt pavement in South Korea. Initially, aggregate quality tests were conducted on mudstone samples to assess their suitability compared to standard criteria. To enhance the visibility and color retention of colored asphalt, addition of pigment in the colored asphalt pavement mixture was considered and evaluated. The asphalt mixtures were evaluated for deformation, crack and viscoelastic properties using the Kim test, indirect tensile (IDT) strength test, and dynamic modulus test, respectively. Results showed that mudstone aggregate exceeded quality standards and the colored asphalt mixtures demonstrated superior deformation strength and crack resistance compared to typical SMA. However, the addition of pigment slightly reduced these properties. Overall, the findings suggest mudstone aggregate as a viable alternative for constructing colored asphalt pavements, offering potential improvements in durability and color retention.